IV Charity International Symposium of Functional Dentistry. Abstracts Association of Orthodontists of Ukraine - Kondratets К. В. (Actual Dentistry, 2024)
IV Charity International Symposium of Functional Dentistry. Abstracts Association of Orthodontists of Ukraine